Epidemiology and clinical features of emergency department patients with suspected COVID‐19: Initial results from the COVID‐19 Emergency Department Quality Improvement Project (COVED‐1). (18th May 2020) - O'Reilly, Gerard M; Mitchell, Rob D; Rajiv, Prithi; Wu, Jamin; Brennecke, Helen; Brichko, Lisa; Noonan, Michael P; Hiller, Ryan; Mitra, Biswadev; Luckhoff, Carl; Paton, Andrew; Smit, De Villiers; et al.
Abstract: Objective: The COVID‐19 Emergency Department (COVED) Quality Improvement Project aims to provide regular and real‐time clinical information to ED clinicians caring for patients with suspected and confirmed COVID‐19. The present study summarises data from the first 2 weeks of the study. Methods: COVED is an ongoing prospective cohort study that commenced on 1 April 2020. It includes all adult patients presenting to a participating ED who undergo testing for SARS‐CoV‐2. Data are collected prospectively and entered into a bespoke registry. Outcomes include a positive SARS‐CoV‐2 polymerase chain reaction test result and requirement for intensive respiratory support. Results: In the period 1–14 April 2020, 240 (16%) of 1508 patients presenting to The Alfred Emergency and Trauma Centre met inclusion criteria. Of these, 11 (5%) tested positive for SARS‐CoV‐2. The mean age of patients was 60 years and the commonest symptoms were acute shortness of breath ( n = 122 [67%]), cough ( n = 108 [56%]) or fever ( n = 98 [51%]). Overseas travel or known contact with a confirmed case was reported by 24 (14%) and 16 (10%) patients, respectively. Fever or hypoxia was recorded in 23 (10%) and 11 (5%) patients, respectively. Eleven (5%) patients received mechanical ventilation in the ED, of whom none tested positive for SARS‐CoV‐2. Conclusions: Among patients presenting to a tertiary ED with suspected COVID‐19, only a small proportion tested positive for SARS‐CoV‐2. Although the low incidence of positive cases currently precludes the development of predictive tools, the COVED Project demonstrates that the rapid establishment of an agile clinical registry for emergency care is feasible. Abstract : COVID‐19 Emergency Department (COVED) Quality Improvement Project reports the findings of the Project's first 2 weeks. Among patients presenting to a tertiary ED with suspected COVID‐19, only a small proportion had a positive test for SARS‐CoV‐2. Although the low incidence of SARS‐CoV‐2 positive cases currently precludes the development of predictive tools, the COVED Project demonstrates that the rapid establishment of an agile clinical registry for emergency care is feasible.